Prior term delivery increases risk of subsequent recurrent preterm birth: An unexpected finding. (27th February 2022) - Suff, Natalie; Xu, Vicky X.; Dalla Valle, Giorgia; Carter, Jenny; Brennecke, Shaun; Shennan, Andrew
Abstract: Background: Women with a prior pregnancy at term are generally considered to be at reduced risk for subsequent spontaneous preterm birth (sPTB), whereas a previous sPTB is a major predictor for a future sPTB. Aims: The objective of this study was to investigate the risk of recurrent sPTB in women with a prior term birth and a subsequent sPTB. Materials and Methods: This is a retrospective cohort study conducted at St Thomas' Hospital in London, UK. There were 430 women included: 230 with a term birth (caesarean section or vaginal delivery) preceding a sPTB (term + sPTB group) and 200 with a prior sPTB only (sPTB only group). The primary outcome was sPTB, <37 weeks gestation. Results: Of the term + sPTB group, 38.7% (89/230) had a recurrent sPTB compared to 20% (40/200) in the sPTB only group ( P < 0.0001), with a relative risk (RR) of 1.9. Of women who had a term caesarean section and a subsequent PTB, 50% (30/60) had a further sPTB (RR 2.5 compared to the sPTB only group), while 34.7% (59/170) of women who had a term vaginal birth and subsequent sPTB, had a further sPTB (RR 1.7 compared to the sPTB only group). Conclusion: In women who have had a previous sPTB, the risk of a recurrence is much higher than in women with a prior term birth. The aetiology of PTB may be different in this subgroup of women and needs to be further elucidated to determine how best to identify and treat them.